2005
DOI: 10.1007/s00737-005-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ attachment style and early experiences: a gender difference

Abstract: We examined gender differences in perceived rearing and adult attachment style in adolescents. A total of 3,912 senior college students (1,149 men and 2,763 women) ages 18-23 (men's M = 20.1 years, women's M = 20.0 years) were administered a set of questionnaires including Relationship Questionnaire (to measure adult attachment), the Parental Bonding Instrument (perceived rearing), and a list of early life events. In the men, positive adult total attachment style was predicted by the scores of paternal care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
47
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 30 publications
13
47
1
1
Order By: Relevance
“…The child is socially isolated; he/she fears abandonment or abuse and feels emotionally vulnerable. The above findings are in accordance to research studies such as the one conducted by Matsuoka [21] who showed that total attachment style was predicted by scores of paternal and maternal bonding. Thus, the adults' attachment style was predictable of early experiences but there existed some gender differences.…”
Section: Discussionsupporting
confidence: 92%
“…The child is socially isolated; he/she fears abandonment or abuse and feels emotionally vulnerable. The above findings are in accordance to research studies such as the one conducted by Matsuoka [21] who showed that total attachment style was predicted by scores of paternal and maternal bonding. Thus, the adults' attachment style was predictable of early experiences but there existed some gender differences.…”
Section: Discussionsupporting
confidence: 92%
“…During the process of analysis, the 7-point scores were also recoded from 0-6. Matsuoka et al (2006) reported the psychometric property of the Japanese version of the RQ and proposed a single-factor structure using the exploratory factor analysis. In the prior studies, total attachment score (TAS) was calculated by subtracting the fearful, preoccupied, and dismissing scores from the secure score, with a higher score indicating a more secure attachment style (Liu, Shono, & Kitamura, 2008;Matsuoka et al, 2006).…”
Section: Measurementmentioning
confidence: 99%
“…The validation of the RQ was reported based on multiple measures of attachment including interview measures (Bartholomew & Horowiz, 1991;Griffin & Batholomew, 1994). Matsuoka et al (2006) reported the psychometric properties of the Japanese version of the RQ and the singlefactor structure was proposed by an exploratory factor analysis with Promax rotation. Therefore, Total Attachment Score (TAS) was calculated by subtracting the Fearful, Preoccupied and Dismissing scores from the Secure score, with a higher TAS indicating more secure adult attachment (Matsuoka et al, 2006).…”
Section: Questionnairesmentioning
confidence: 99%
“…In order to confirm the single-factor structure originally proposed by Matsuoka et al (2006), we performed confirmatory factor analysis of RQ using AMOS 6.0. The singlefactor structure of RQ was supported by GFI = .995, AGFI = .973, RMSEA = .073, indicating a good fit.…”
Section: Confirmatory Factor Analyses Of Rqmentioning
confidence: 99%